A disintegrin and metalloproteinase 12 (ADAM12) is reduced at 36 weeks' gestation in pregnancies destined to deliver small for gestational age infants. (January 2022) - Andres, Faith; Wong, Georgia P.; Walker, Susan P.; MacDonald, Teresa M.; Keenan, Emerson; Cannon, Ping; Nguyen, Tuong-Vi; Hannan, Natalie J.; Tong, Stephen; Kaitu'u-Lino, Tu'uhevaha J.
Abstract: First trimester circulating ADAM12 is reduced in fetal growth restriction (FGR) and preeclampsia. We measured plasma ADAM12 at 36 weeks' gestation preceding diagnosis of term preeclampsia or delivery of a small for gestational age (SGA; birthweight <10th centile) infant in two independent cohorts (Cohort 1 90 SGA, 41 preeclampsia, 862 controls; Cohort 2121 SGA 23 preeclampsia; 190 controls). ADAM12 was reduced with SGA in both cohorts (p = 0.0015 and 0.011 respectively), and further reduced with birthweight <5th centile (p = 0.0013 and 0.0058 respectively). This validates ADAM12 as an SGA biomarker near term. Circulating ADAM12 preceding preeclampsia was not consistently altered. Highlights: ADAM12 is reduced at 36 weeks' gestation in infants born small for gestational age. ADAM12 is not consistently changed at 36 weeks preceding preeclampsia diagnosis. ADAM12 may hold promise for combination with other biomarkers to predict SGA/FGR.